Comparison of positioning errors and PTV expansion between the iSCOUT image-guidance system and onboard EPID in rectal cancer radiotherapy: a real-world study - Wan, Bao; Hou, Lu; Han, Jiangtao; Zheng, Yongtai; Liu, Chao; Sun, Shuo; Zhao, Yu; Huan, Fukui; Wang, Hongkai; Li, Tantan (Frontiers in Oncology, 2026)
IntroductionThe iSCOUT orthogonal imaging system and onboard EPID system are commonly used for image-guidance positioning in conventional linear accelerators, but studies comparing the two are scarce. This research aims to analyze and compare the differences and consistency between the iSCOUT and onboard EPID systems in rectal cancer patients in the prone position.MethodsA retrospective analysis was conducted on 277 rectal cancer patients positioned prone on a Belly Board. During radiotherapy, at least three position verifications were performed in the first week, followed by weekly verifications. Both iSCOUT and onboard EPID image-guidance systems were used simultaneously for these verifications. Systematic and random errors, as well as the consistency of fixed positioning, were evaluated based on images from both systems taken in the same position. Patients were grouped by tumor location, BMI, age, and gender. The positioning errors and PTV (Planning Target Volume) margins for each group were calculated to analyze relevant patterns.ResultsKappa consistency in the leftright (LR) and superior-inferior (SI) directions was better compared to the anterior-posterior(AP) direction (LR = 0.794, SI = 0.852, AP = 0.610). Patients with tumors located in the upper rectal location require larger PTV expansions compared to those with middle or lower tumors. Obese patients with a BMI≥28 exhibited significantly larger PTV expansions than other groups. Age based grouping revealed an inverse relationship between age and PTV margin expansion. No significant differences were observed when grouped by gender.DiscussionThe iSCOUT and EPID systems demonstrate good clinical agreement. Optimal PTV margins in rectal cancer radiotherapy should be individualized, with special consideration given to tumor location (upper rectum), high BMI, and advanced patient age.